Love under Cuban skies - Champagne, Wendy; MacDonald, Ann-Marie, 1958-; E2F Film Inc.; Esperamos (Firm); Soundview Media Partners ([Toronto] : E2F Film Inc., 2014)
Canadian women are not shy about holiday flings, especially where Cuban men are concerned. For some it's just mojitos and a mombo but when true love blooms it's a delicate dance indeed. Impoverished Cubans want exit visas. Empowered Canadian women want attentive young husbands. Love Under Cuban Skies is an exploration of female sex tourism in Cuba and the story of 3 Canadian women and their Cuban lovers. Who is exploiting whom? Seen and heard are Amalia Cabezas, Sociologist and Author, Economies of Desire; Lee Cohen, Immigration and Human Rights Lawyer; Christian and Samuel, Cuban Entertainers; Canadian Tourists Roxanne, Chanel, Mary and Martina; Jill Arnott, her Cuban husband Yandy, Jill's mother Kathy, and sister Kerri; Claire and her Cuban husband who left her; American Paula and her younger Cuban husband Andy; and Cuban Hineteros (jockeys) Ramon & Yosmel and Yosmel's mother Sylvia. Locations include Canada, America and Cuba.
Narrator: Ann-Marie MacDonald.
Originally released as a television program in 2014.
Director: Champagne, Wendy ; Coordinating Producer: Couture, Isabelle.
Cinematographer, Katerine Giguère ; editor, Heidi Haines ; music, Olivier Alary.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 15, 2019)
Keywords: Sex tourism -- Cuba; Tourists -- Sexual behavior -- Cuba; Women travelers -- Sexual behavior -- Cuba; Cuba -- Social conditions -- 1990-; Documentary television programs; Nonfiction films; Internet videos; Streaming video